Fermentasi Kulit Singkong Sebagai Pakan Alternatif Pengganti Hijauan Saat Kemarau Di Desa Bandungrejo, Kecamatan Ngablak, Kabupaten Magelang - Daffa Naufal Rafif; Lintang Nariswari; Luky Widiyanto; Muhammad Herfa Setiawan; Nova Fahrizal Hidayat (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2024)
The purpose of the community service in Bandungrejo Village is to provide feed processing technology that produces higher nutritional content and increases the shelf life of feed. A commonly used method to increase the shelf life of feed is fermentation. Fermented feed can use agricultural waste in the form of cassava peel. Through training and counselling on making cassava peel fermented feed, it is hoped that it can increase the shelf life of feed and reduce feed limitations during the dry season. With the training on making fermented feed using cassava peel, it is expected that a reduction in animal feed costs and an increase in the productivity of livestock will occur. Training in making fermented animal feed can also improve community skills in innovating to make alternative feed. This community service activity shows that independently produced animal feed can reduce dependence and has the potential to replace forage feed with a variety of higher quality feeds.